The long-run relationship between the construction sector and the national economy in Cape Verde - Lopes, Jorge; Nunes, Alcina; Balsa, Carlos (International Journal of Strategic Property Management, 2011)
The relationship between a country's level of activity in the construction industry and its stage of economic development is a complex one. Several studies over the last forty years, based mainly on cross sectional data, found a positive association between national income and several measures of the construction industry activity. early studies were concerned with the role of the construction sector, as part of physical capital, in the promotion of economic growth and development. a dominant paradigm that later emerged is the ‘Bon curve’ or the inverted U-shaped pattern of development. More recent research, based on longitudinal analysis, has also pointed to the non-linear relationship between the share of construction in GDP and the level of income per capita. Using time-series data drawn from the United nations, this study applies an econometric methodology to assess the validity of the underlying propositions in a low-middle income economy-Cape Verde—over the long period of 38 years. The findings are in line with the assumptions that in the upward growth trend in developing countries, the pattern of the construction industry tends to follow that of the general economy.First Publish Online: 14 Apr 2011